Comparison of anthropometric indices of obesity to predict dyslipidaemia among medical students - Chatuvedi, Sourav; Wanjari , Anil; Lahole, Swapnil; dubey, Ayush (International Journal of Psychosocial Rehabilitation, 2020)
Obesity is a global epidemic threatening healthy population in increasing number of countries. In developed countries prevalence of obesity is rising because of decrease physical work, increase consumption of junk food and alcohol and discrepancy between consumption of energy and utilisation of energy Obesity. Anthropometric parameters are better tool in clinical practice of being a easy to take reading and measurements with good reproducibility, especially in country like India. This study is done to determine the prevalence of obesity and dyslipidaemia among medical students and to study the risk factors for obesity and dyslipidaemia among medical studentsTo determine the prevalence of obesity and dyslipidaemia among medical students.The study the risk factors for obesity and dyslipidaemia among medical student we did a cross sectional study in 100 medical students. Participants were subjected to anthropometric measurements such as height, weight, waist circumference (WC), and hip circumference using standard procedures on the same morning of the day, as the blood sample was collected after overnight fast and estimated for fasting blood sugar and lipid profile.Expected Results and Conclusion- lipid profile best reflect by using anthrometric parameter i.e WC. In a developing country like India, where measurement of cardiovascular risk factors such as body fat saturation and lipid profile remains difficult in the rural population, WC may be used as an effective tool, without being used as a substitute